2009
DOI: 10.1002/cmdc.200800424
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Functionalized Ultrasmall Superparamagnetic Nanoparticles as Magnetic Delivery Vectors for Camptothecin

Abstract: Scheme 1. Reagents and conditions: a) camptothecin, EDC, DMAP, CH 2 Cl 2 , RT, o/n; b) TFA/CH 2 Cl 2 (1:1), RT, 40 min; c) EDC, HOBt, aminoPVA, DMF/H 2 O, RT, 1 d; d) ferrofluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…The therapeutic agent can also be attached directly onto the IONP surface. Gendeli and coworkers [78] covalently attached an anti-cancer drug (amptothecin) to USPIOs (core diameter, 9-10 nm; hydrodynamic diameter, 52 nm) coated with polyvinylalcohol/polyvinylamine using a biodegradable linkage. Th e magnetic properties of the nanoparticles were exploited to enhance cell uptake.…”
Section: Drug and Gene Deliverymentioning
confidence: 99%
“…The therapeutic agent can also be attached directly onto the IONP surface. Gendeli and coworkers [78] covalently attached an anti-cancer drug (amptothecin) to USPIOs (core diameter, 9-10 nm; hydrodynamic diameter, 52 nm) coated with polyvinylalcohol/polyvinylamine using a biodegradable linkage. Th e magnetic properties of the nanoparticles were exploited to enhance cell uptake.…”
Section: Drug and Gene Deliverymentioning
confidence: 99%
“…The culture media were replaced with fresh medium containing nanogels diluted in complete medium and the cells were exposed to the nanogels for 24 h. Then, medium was replaced with complete medium without nanogels and the cell viability was evaluated using the MTT assay, essentially as previously described [31]. Briefly, MTT (3-(4,5-dimethyl-2-thiazoyl)-2,5-diphenyltetrazolium bromide, Roche, Mannheim, Germany, 250 μg/mL final concentration) was added to the cells for 2 h, then the cell culture supernatants were removed, the cell layers were dissolved in 2-propanol/ 0.04 N HCl and absorbance at 540 nm was measured (iEMS Reader MF, Labsystems, Bioconcept, Switzerland) and compared to the values of control cells incubated without nanogels.…”
Section: Determination Of Cytotoxicitymentioning
confidence: 99%
“…Briefly, MTT (3-(4,5-dimethyl-2-thiazoyl)-2,5-diphenyltetrazolium bromide, Roche, Mannheim, Germany, 250 μg/mL final concentration) was added to the cells for 2 h, then the cell culture supernatants were removed, the cell layers were dissolved in 2-propanol/ 0.04 N HCl and absorbance at 540 nm was measured (iEMS Reader MF, Labsystems, Bioconcept, Switzerland) and compared to the values of control cells incubated without nanogels. Alternatively for non-adherent human THP-1 macrophages, the alamarBlue assay was performed, as previously described [31]. Briefly, cells were exposed to 10% Alamar Blue (Serotec, Düsseldorf, Germany) added to the cell culture medium and fluorescence increase was directly measured in a multiwell fluorescence reader (λ ex /λ em =530 nm/580 nm) after 2 h at 37°C.…”
Section: Determination Of Cytotoxicitymentioning
confidence: 99%
“…Their experimental results showed a distinct pattern of Zeta potential change that allows the discrimination of normal human breast epithelial cells from breast cancer epithelial cells, where the tumor-homing F3 peptide was specifically bound to nucleolin receptors that are overexpressed in breast cancer cells. Cengelli et al [40] presented the linkage of therapeutic drugs to iron oxide nanoparticles, allowing the intracellular release of the active drug via cell-specific mechanisms. The drug-conjugated nanoparticles exhibited antiproliferative activity in vitro against human melanoma cells and resulted in tumor-selective and magnetically enhanced drug delivery.…”
Section: Iron Oxidesmentioning
confidence: 99%
“…Cengelli et al [40] demonstrated that a hierarchical building of a covalent drug-USPIO assembly is possible, even for highly hydrophobic drugs like camptothecin (CPT). The amount of CPT-USPIO taken up by human Me300 melanoma cells after 16 and 36 h as a function of the number of added nanoparticles was determined from the amount of cell-associated iron and cell-associated CPT fluorescence (figures 11(a) and (b)) as compared with that of the previously described aminoPVA-USPIOs [86].…”
Section: Inorganic Nanoparticles For Drug Deliverymentioning
confidence: 99%